Analyzing the Historical Evolution, Contemporary Debates, and Global Perspectives on the Death Penalty and its Abolition - Agung Zulfikri; Sabil Mokodenseho; Supriandi Supriandi (Westscience Press, 2023)
This research method outlines a comprehensive bibliometric analysis of the scholarly literature on the historical evolution, contemporary debates, and global perspectives regarding the death penalty and its abolition. Using bibliometric techniques, this study aims to provide insights into trends, patterns, and influences within this field of research. The method includes selecting relevant databases, search terms, data extraction, and analysis. The results of this bibliometric analysis contribute to a better understanding of the scholarly landscape surrounding the death penalty, facilitating future research and policy decisions on this significant social issue.